2010
DOI: 10.28945/1323
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and Learning for Management Information Systems

Abstract: Previous research has established that users need competence in both computing and the context of the software. Information systems often fail due to low competence amongst users, and no study is known to provide a systematic account of the user competence needed. This research concerns competence needs amongst prospective users of a computerised management information system where there is no operational computer based IS from which to obtain data. The study shows that three subject matter areas of user compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In the context of this research, users are managers who are directly involved in planning, designing, managing accounting information systems, in this case financial applications. This concept has been proven through previous research [8], [9] and [10].…”
Section: Introductionmentioning
confidence: 61%
“…In the context of this research, users are managers who are directly involved in planning, designing, managing accounting information systems, in this case financial applications. This concept has been proven through previous research [8], [9] and [10].…”
Section: Introductionmentioning
confidence: 61%
“…Beyond this direct contribution to design of an ICT solution, the study has also contributed to the discourse in HIS in developing countries by emphasizing the crucial role of the front line health workers’ own problem solving, invention and adaptation of information tools. Thus, our study adds to the HIS literature that focusses on health workers’ learning activities (Kaasbøll et al , 2010). Specifically, we demonstrated how health workers learn through their interactions with the context and further adapt information tools and work practices to fit their working situations.…”
Section: Implications and Conclusionmentioning
confidence: 95%
“…al (2011) prove that manager competence is the most influential factor on the quality of financial application (MAIS) in companies listed on the Tehran Stock Exchange. Furthermore, Kaasbøll et. al (2010) found that low competence impacts financial application (MAIS) that often fails.…”
Section: Introductionmentioning
confidence: 99%